SMART HOME ENERGY SAVING WITH BIG DATA AND MACHINE LEARNING - Ahmad, Hawar Bahzad; Asaad, Renas Rajab; Almufti, Saman M; Hani, Ahmed Alaa; Sallow, Amira Bibo; Zeebaree, Subhi R. M. (LPPM Universitas Jambi, 2024)
In response to escalating energy consumption, particularly within the housing sector, a global imperative to reduce energy usage has emerged, propelling the concept of